Formation of Ideological (Official and Religious) Discourses as Basis for Ryacudu’s Securitization of LGBT Acts in Indonesia 2016 – 2017 - Wahyu Arif Raharjo (JPW (Jurnal Politik Walisongo), 2022)
Despite its existence in various local traditions, LGBT acts in Indonesia has recently faced notorious condemnation and abuse. This paper explores minister Ryacudu’s discourse formation in removing LGBT issue from normal politics into security sector, and whether such action has been successful in convincing audience that LGBT is indeed a security issue. In doing so, this study utilizes securitization framework to unravel the rationalization of removing LGBT into security sector and how it relates to Indonesian identity discourse. This paper argues that securitization of LGBT acts in Indonesia is an enactment of national and religious identity. LGBT has been re-constructed as a threat to national identity, thus, a societal security threat. This securitization is conducted by Indonesian government, initially started by Minister Ryacudu’s call to reject LGBT, which is then widely echoed among citizens. Statement from Ryacudu is the main speech act, supported by, utilization of religious values and national heteronormative identity as reference values to legitimize extraordinary measures to the so-called ‘LGBT problem’. The ‘extraordinary measures’ taken to ‘protect’ Indonesia’s identity include various sectors from education, communication and media, and commerce. Wide acceptance among citizen suggests that Indonesian government, especially Minister Ryacudu have successfully securitized LGBT issue in Indonesia.